Simulation study on the application of reactive distillation (RD) column for producing ethyl acetate via esterification of acetic acid with ethanol - Murgan, V. K.; Abdul Mutalib, M. I. (2006)
Reactive distillation (RD) is an attractive way of improving process economics by combining distillation and reaction, especially for equilibrium limited reactions such as esterification. In this work, a simulation model for esterification of acetic acid by ethanol in a RD column was developed and verified against published data. Upon confirming the applicability of the simulation model, the effects of changing various operating and design parameters on the column performance were studied. It was found that independent changes in several parameters should enhance the overall conversion and purity. However it was discovered that the performance of the column could not be enhanced significantly with conventional RD column. Finally, a new configuration that involves the introduction of extractive zones in the RD column with extraneous component as an extractive agent was proposed. It was found that higher conversion and significant product purity enhancement could be attained with new configuration as compared to the conventional RD column.